Taking HIV Testing to Families: Designing a Family-Based Intervention to Facilitate HIV Testing, Disclosure and Intergenerational Communication - Heidi van Rooyen; Zaynab Essack; Zaynab Essack; Tamsen Rochat; Tamsen Rochat; Tamsen Rochat; Tamsen Rochat; Daniel Wight; Lucia Knight; Ruth Bland; Ruth Bland; Ruth Bland; et al. (Frontiers Media S.A., 2016)
Introduction: Facility-based HIV testing does not capture many adults and children who are at risk of HIV in South Africa. This underscores the need to provide targeted, age-appropriate HIV testing for children, adolescents and adults who are not accessing health facilities. While home based counseling and testing has been succesfully delivered in multiple settings, it also often fails to engage adolescents. To date, the full potential for testing entire families and linking them to treatment has not been evaluated. Methods: The steps to expand a successful home-based counseling and testing model to a family-based counseling and testing approach in a high HIV prevalence context in rural South Africa are described. The primary aim of this family-based model is to increase uptake of HIV testing and linkage to care for all family members, through promoting family cohesion and intergenerational communication, increasing HIV disclosure in the family, and improving antiretroviral treatment uptake, adherence and retention. We discuss the three-phased research approach that led to the development of the family-based counseling and testing intervention. Results: The family-based intervention is designed with a maximum of five sessions, depending on the configuration of the family (young, mixed and older families). There is an optional additional session for high-risk or vulnerable family situations. These sessions encourage HIV testing of adults, children and adolescents and disclosure of HIV status. Families with adolescents receive an intensive training session on intergenerational communication, identified as the key causal pathway to improve testing, linkage to care, disclosure and reduced stigma for this group. The rationale for the focus on intergenerational communication is described in relation to our formative work as well as previous literature, and potential challenges with pilot testing the intervention are explored. Conclusion: This paper maps the process for adapting a novel and largely successful home-based counseling and testing intervention for use with families. Expanding the successful home-based counseling and testing model to capture children, adolescents and men could have significant impact if the pilot is successful and scaled-up.